PARTICIPATIVE SCHOOL MANAGEMENT: A PATH TO AUTONOMY (Interdisciplinary Studies Journal, 2023)
This article aims to provide a theoretical reflection on the centrality of participative school management, with the horizon of pursuing school autonomy and its sociopolitical subjects that compose it (school staff, students, teachers, and the community). The objective is to highlight how participation is a crucial element in achieving school autonomy. To develop this discussion, without aiming to exhausting it, a qualitative approach was adopted based on a bibliographic review of the subject, drawing on the theoretical foundations of Libâneo (2013) and Lück (2000). The bibliographic research conducted emphasizes the importance of the participation of the actors comprising the school community in their quest for protagonism. It is argued that autonomy constitutes a fundamental premise in the process of participative management, with an ongoing tension between the local scale and the broader context in which the school community is embedded.
Keywords: Participation; Participative management; School Autonomy